RELATIONSHIP OF THE RELIGIOUSITY LEVEL WITH THE QUALITY OF SOCIAL INTERACTION AND IMPLICATIONS IN THE DEVELOPMENT OF IMPLEMENTATION PROGRAMS GUIDANCE AND COUNSELING SERVICES - Afsetubest Afroe; Mudjiran Mudjiran (Universitas Negeri Padang, 2019)
This research is a correlational research. This research aims to find out whether there is a relationship of religiosity with social interaction of peers in SMn 1 Airpura. Testing the hypothesis in this study using statistical analysis using SPSS 16.0. The population in this study were students at 1Airpura High School consisting of 625 people using a stratified random sampling with a total of 244 people. The results of this study are (1) The level of religiosity of Airpura 1 N High School students is in the medium category. Hereby shows that the students of SMA N 1 Airpura are quite good in their level of religiosity, (2) The social interaction of students of SMA N 1 Airpura is in the medium category. This shows that students of SMA N 1 Airpura have good social interactions in their daily lives and also during their time at school, (3) There is a significant positive relationship between the significant level of religiosity and social interaction at SMA N 1 Airpura. This means that the higher the level of religiosity, there is a tendency for higher social interaction carried out by Airpura N 1 High School students. Conversely, the lower the level of religiosity there is a tendency for the lower social interactions undertaken by Airpura 1 N High School students.